Intermittent vs. continuous tests for monitoring swimming performance: A systematic review with meta-analysis - FEITOSA, W. G.; CASTRO, F. A. D. E. (Journal of Physical Education and Sport, 2024)
Approach: Intermittent incremental tests (ITT), intermittent tests (IT), and continuous tests (CT) provide physiological parameters along with the corresponding swimming speeds (v), which are valuable for decision making by coaches.